Carbon Dots: Near‐Infrared Excitation/Emission and Multiphoton‐Induced Fluorescence of Carbon Dots (Adv. Mater. 13/2018). Issue 13 (30th March 2018) - Li, Di; Jing, Pengtao; Sun, Lihuan; An, Yang; Shan, Xinyan; Lu, Xinghua; Zhou, Ding; Han, Dong; Shen, Dezhen; Zhai, Yuechen; Qu, Songnan; Zbořil, Radek; et al.
Abstract : Both a near‐infrared (NIR) absorption band and enhanced NIR fluorescence are realized by Songnan Qu, Andrey L. Rogach, and co‐workers, in article number 1705913, through surface engineering of carbon dots, exploiting electron‐acceptor groups, namely molecules or polymers rich in sulfoxide/carbonyl groups. Twophoton‐induced NIR emission and three‐photon‐induced red emission are simultaneously observed for carbon dots in dimethyl sulfoxide under excitation of a 1400 nm femtosecond pulse laser in the NIR‐II window.